EXPLORING LOCAL WISDOM VALUES OF SOUTH NIAS FOR THE DEVELOPMENT OF A CONSERVATION-BASED SCIENCE CURRICULUM - Harefa, Darmawan (TUNAS : Jurnal Pendidikan Biologi, 2024)
This study aims to explore the local wisdom values of the Nias Selatan community and investigate the potential integration of these values into a conservation-based Science curriculum. The method employed is literature study, which includes the analysis of documents, articles, and relevant sources regarding local wisdom and environmental education. The results indicate that the local wisdom of Nias Selatan, such as sustainable agricultural practices and marine resource management, embodies important values that align with conservation principles. Integrating these values into the Science curriculum can not only enhance students' understanding of the environment but also foster a caring attitude towards sustainability. Despite challenges in implementation, such as a lack of resources and teacher training, recommendations for the development of a conservation-based curriculum are proposed. This research is expected to contribute to efforts in environmental preservation and the development of relevant education in Nias Selatan.